2014
DOI: 10.1186/2045-3701-4-28
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy protects against palmitate-induced apoptosis in hepatocytes

Abstract: BackgroundNon-alcoholic fatty liver disease, one of the most common liver diseases, has obtained increasing attention. Palmitate (PA)-induced liver injury is considered a risk factor for the development of non-alcoholic fatty liver disease. Autophagy, a cellular degradative pathway, is an important self-defense mechanism in response to various stresses. In this study, we investigated whether autophagy plays a protective role in the progression of PA-induced hepatocytes injury.ResultsAnnexin V-FITC/PI staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
6
42
0
Order By: Relevance
“…Thus, lipophagy impairment due to LRP1 deficiency may account for the increased sensitivity of hLrp1 Ϫ/Ϫ hepatocytes to palmitate-induced apo- ptosis. Previous studies have shown that lipophagy protects hepatocytes against oxidant stress and lipotoxicity (40,41). Thus, our observations that the elevated reactive oxygen species production and reduced viability of palmitate-treated hLrp1 Ϫ/Ϫ hepatocytes, which can be improved by the cysteine protease inhibitor E64D, provided additional support for the interpretation that LRP1 deficiency in hepatocytes impairs lipophagy to promote palmitate-induced lipid accumulation, lysosomal permeabilization, mitochondrial dysfunction, ER stress, and apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, lipophagy impairment due to LRP1 deficiency may account for the increased sensitivity of hLrp1 Ϫ/Ϫ hepatocytes to palmitate-induced apo- ptosis. Previous studies have shown that lipophagy protects hepatocytes against oxidant stress and lipotoxicity (40,41). Thus, our observations that the elevated reactive oxygen species production and reduced viability of palmitate-treated hLrp1 Ϫ/Ϫ hepatocytes, which can be improved by the cysteine protease inhibitor E64D, provided additional support for the interpretation that LRP1 deficiency in hepatocytes impairs lipophagy to promote palmitate-induced lipid accumulation, lysosomal permeabilization, mitochondrial dysfunction, ER stress, and apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…Increasing reports shows that autophagy has a protective effect on liver injury [26][27][28]. Ni et al found that autophagy protected hepatocytes against acetaminophen (APAP)-induced necrosis, whereas the treatment of 3-MA or CQ further exacerbated necrosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this protective effect was mediated by enhanced mitophagy, which reduced cytochrome c release and caspase activation [48]. Similar protective effects of enhanced autophagy were also demonstrated in palmitate-induced apoptosis in hepatocytes or oxidative stress-induced apoptosis in a rat model of Parkinson's disease [4950]. However, when excessive toxic signals threaten cells beyond this defense, ultimately apoptosis as well as autophagic cell death result.…”
Section: Part Imentioning
confidence: 92%